Analisis Hukum terhadap Penetapan Ahl Waris Pengganti Menurut KHI (Kompilasi Hukum Islam) - Anita Anita (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
This paper discusses the Islamic inheritance system, especially substitute heirs by focusing on The Determination of PA Makassar No. 3 / Pdt.P / 2011 / PA. Mks. The discussion will focus on two things, are: (1) the position of grandchildren as substitute heirs in the Islamic inheritance system according to the Compilation of Islamic Law, and (2) judicial legal considerations in determining substitute heirs in accordance with Compilation of Islamic Law. At the end of the paper, there are two things are concluded. First, Article 185 KHI explains that grandchildren can occupy the position of substitute heirs and change the position of their parents, and will receive the inheritance portion of a number of shares obtained by their parents if he were still alive. Second, distribution of inheritance, normatively, can only be done according to the provisions contained in the Qur'an and hadith. But in fact often the people in the distribution of inheritance do it peacefully, and have been accommodated by Article 183 Compilation of Islamic Law.